How to Teach English to Adult Learners (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Teaching English to adult learners requires a different approach compared to teaching younger students. Adult learners often have specific needs and learning styles that must be taken into consideration when designing a curriculum and lesson plans. This article will provide tips and strategies for teaching English to adult learners, including how to address their specific needs, overcome challenges, and create a supportive and inclusive learning environment. By understanding the unique characteristics of adult learners and tailoring the teaching approach accordingly, educators can effectively help adult learners improve their English language skills and achieve their communication goals.